Hyperopic correction: clinical validation with epithelium-on and epithelium-off protocols, using variable fluence and topographically customized collagen corneal crosslinking - Kanellopoulos AJ (Dove Medical Press, 2014)
Anastasios John Kanellopoulos,1,2 George Asimellis1 1LaserViison.gr Clinical and Research Eye Institute, Athens, Greece; 2Department of Ophthalmology, New York University Medical School, New York, NY, USAPurpose: To report novel application of topographically-customized collagen crosslinking aiming to achieve hyperopic refractive changes. Two approaches were evaluated, one based on epithelium-off and one based on epithelium-on (transepithelial). Methods: A peripheral annular-shaped topographically customizable design was employed for high-fluence ultraviolet (UV)-A irradiation aiming to achieve hyperopic refractive changes. A total of ten eyes were involved in this study. In group-A (five eyes), a customizable ring pattern was employed to debride the epithelium by excimer laser ablation, while in group-B (also five eyes), the epithelium remained intact. In both groups, specially formulated riboflavin solutions were applied. Visual acuity, cornea clarity, keratometry, topography, and pachymetry with a multitude of modalities, as well as endothelial cell counts were evaluated. Results: One year postoperatively, the following changes have been noted: in group-A, average uncorrected distance visual acuity changed from 20/63 to 20/40. A mean hyperopic refractive increase of +0.75 D was achieved. There was some mild reduction in the epithelial thickness. In group-B, average uncorrected distance visual acuity changed from 20/70 to 20/50. A mean hyperopic refractive increase of +0.85 D was achieved. Epithelial thickness returned to slightly reduced levels (compared to baseline) in group-A, whereas to slightly increased levels in group-B. Conclusion: We introduce herein the novel application of a topographically-customizable collagen crosslinking to achieve a hyperopic refractive effect. This novel technique may be applied either with epithelial removal, offering a more stable result or with a non-ablative and non-incisional approach, offering a minimally invasive alternative.Keywords: topography customizable crosslinking, high-fluence cross linking, epi-on and epi-off CXL, PiXL, KXL II, CXL hyperopic correction, CXL presbyopic correction